2007
DOI: 10.1111/j.1743-7563.2007.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of cognitive function in patients with early breast cancer receiving adjuvant chemotherapy

Abstract: Aim:To assess cognitive function prospectively in women with early breast cancer before, during and after the administration of adjuvant chemotherapy. Methods: Between May 2000 and November 2001, 35 assessable patients were entered into the study. Thirty-one received oral cyclophosphamide, methotrexate and 5-fluorouracil (CMF) and four received epirubicin and cyclophosphamide followed by CMF ((cyclophosphamide, methotrexate and 5-fluorouracil)). Testing consisted of the completion of a battery of neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
(29 reference statements)
3
25
0
Order By: Relevance
“…At T0, Cognitive impairment was noted in 25% (125 of 503) of the breast cancer patients and 10% (12 of 120) of the healthy controls at T0 3 26 , 27 , 36–40 Within the patient group, 24% (108 of 446) of the CT patients were labeled as cognitively impaired, , , , , , compared to 30% (17 of 57) of the no‐CT patients. , At T1, 24% (70 of 295) of the breast cancer patients and 10% (10 of 102) of the healthy controls scored cognitively impaired 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At T0, Cognitive impairment was noted in 25% (125 of 503) of the breast cancer patients and 10% (12 of 120) of the healthy controls at T0 3 26 , 27 , 36–40 Within the patient group, 24% (108 of 446) of the CT patients were labeled as cognitively impaired, , , , , , compared to 30% (17 of 57) of the no‐CT patients. , At T1, 24% (70 of 295) of the breast cancer patients and 10% (10 of 102) of the healthy controls scored cognitively impaired 3 …”
Section: Resultsmentioning
confidence: 99%
“…At T2, 21% (102 of 479) of the breast cancer patients and 7% (10 of 149) of the healthy controls scored cognitively impaired 27 36 , 38–40 , 43 , 44 Within the patient group, 23% (77 of 336) of the CT patients were labeled as cognitively impaired compared to 18% (25 of 143) of the no‐CT patients. Two studies have separately reported nonsystemic (e.g., RT) treatment showing that 17% (14 of 81) of nonsystemic patients scored cognitively impaired 36 …”
Section: Resultsmentioning
confidence: 99%
“…Only prevalence reports from T2 and T3 were subjected to subgroup analyses based on the number of studies contributing data at these time-points, and the number in each analysis when split into sub-groups. At these time-points, four studies were considered to have used less stringent test methods 70 , 75 , 80 , 88 . Heterogeneity remained high after sub-group analysis with the high stringency sub-group having a pooled prevalence of 25% (95% CIs: 16–35), I 2 = 90% at T2, and 23% (95% CIs: 13–34), I 2 = 74% at T3 (Fig.…”
Section: Meta-analysismentioning
confidence: 99%
“…At these time-points, four studies were considered to have used less stringent test methods. [70, 75, 80, 88] Heterogeneity remained high after sub-group analysis with the high stringency sub-group having a pooled prevalence of 25% (95% CIs: 16-35), I 2 = 90% at T2, and 23% (95% CIs: 13-34), I 2 = 74% at T3 (Figure 7).…”
Section: Resultsmentioning
confidence: 99%